Recent advances of edible marine algae-derived sulfated polysaccharides in antiviral treatments: challenges vs. opportunities - Dong, Xiaoying; Qiu, Yusong; Jia, Nan; Wu, Yinfeng; Nie, Qing; Wen, Jiahui; Zhao, Chao; Zhai, Yongzhen (Frontiers in Nutrition, 2025)
Marine polysaccharides, particularly those derived from red, brown, and green algae, have shown promising antiviral activity. Among them, sulfated polysaccharides are particularly notable due to their broad-spectrum antiviral properties. These include direct viral destruction, inhibition of virus adsorption, disruption of viral transcription and replication, and the stimulation of the host’s antiviral immunity. With low toxicity, minimal drug resistance, and excellent biocompatibility, these polysaccharides represent promising candidates for the development of antiviral medications. For instance, carrageenan, a polysaccharide from red algae, and fucoidan, a polymer from brown algae, have both been proven to effectively inhibit viral infections. Sulfated polysaccharides from green algae, such as those found in Ulva species, also exhibit antiviral properties, including activity against the Japanese encephalitis virus. These polysaccharides function by blocking the attachment of viruses to host cells or interfering with various stages of the viral life cycle. Moreover, marine polysaccharides have been shown to enhance host immune responses, thereby aiding in viral clearance. Although these findings highlight the antiviral potential of marine polysaccharides, most studies have been conducted in vitro or in animal models. Further clinical trials are necessary to validate their effectiveness and safety for therapeutic use.